Modulating carboxymethylcellulose-based hydrogels with superior mechanical and rheological properties for future biomedical applications - Dahlan, N. A.; Teow, Sin Yeang *; Lim, Y. Y.; Pushpamalar, Janarthanan (Budapest University of Technology and Economics, 2021)
Herein, a grafted copolymer composed of carboxymethylcellulose (CMC) and polyethylene-glycol-aminated (PEG-NH2) was successfully synthesized via a facile ionic interaction and scalable route in the presence of EDC/NHS (Nethyl-N′-(3-imethylaminopropyl)carbodiimide/N-hydroxysuccinimide) activators. From Fourier transform infrared (FTIR) spectroscopy, the absorption peak at 1652 cm–1 corresponded to –NH groups of PEG-NH2. After grafting, the grafted CMC-PEG was characterized for surface morphology, crystallinity, functional groups determination, and thermal analysis. No cytotoxicity effect was observed in normal human dermal fibroblasts (NHDFs) cells following exposure to the grafted CMC-PEG up to 2 mg/ml. The rheological studies suggested that the optimized 10% (w/v) grafted CMC-PEG hydrogels crosslinked with 5% (w/v) citric acid (CA) exhibited better mechanical properties compared to the non-grafted CMC. This work highlights the characterizations of grafted CMC-PEG and demonstrates the potential of grafted CMC-PEG hydrogels crosslinked with CA for advanced 3D-bioprinting or as injectable hydrogels in various biomedical applications such as tissue engineering, wound dressing materials, and drug delivery systems.